Primary Teachers’ Perspectives on the Effectiveness of Continuous Formative Assessment in Teaching Lower Primary Classes - Yeshi Wangchuk (Bhutan Journal of Research and Development, 2024)
This study explored primary teachers’ experiences and views on the implementation of Continuous Formative Assessment in lower primary classrooms of schools in Trashigang Dzongkhag. A mixed-method approach was used, where data were collected from 85 randomly selected primary teachers through an online survey questionnaire. The questionnaire assessed their knowledge, competencies, current practices, challenges, and perceptions regarding the effectiveness of CFA. Further, six teachers were interviewed using semi-structured interviews to gather more detailed insights. The results indicated that such substantial barriers to effective CFA implementation included competence, heavy workloads, large class sizes, and a lack of implementation guidelines. Equally significant was the dire need for extensive training and professional development programs to overcome these obstacles. These findings give useful insights into helping educators and stakeholders identify impediments to the implementation of CFA and provide practical recommendations for its effective adoption in lower primary classrooms.